APPLICATIONS OF 3D PRINTING TECHNIQUES FOR OCCLUSAL SPLINTS USED IN BRUXISM - Adrian Marcel Popescu; Diana Elena Vlăduțu; Petre Costin Mărășescu; Marina Olimpia Amărăscu; Daniel Adrian Târtea; Sanda Mihaela Popescu; Luana Lascu; Veronica Mercuț (Romanian Journal of Oral Rehabilitation, 2024)
Currently, there are several digital technologies for the manufacture of occlusal appliances used in bruxism, which may involve subtractive technologies or additive technologies. The purpose of the study is the presentation of a digital workflow for occlusal splint through CAD-CAM with 3D printing. Material and method: The technology used for the manufacture of the occlusal splint included as stages: obtaining digital models, creating the digital design of the splint, 3D printing of the splint from a rigid PMMA material, adapting the splint on dental arch and in occlusion. Results: The digital technology for the occlusal appliance was used for a patient with sleep bruxism. The patient wore the occlusal splint for 9 weeks, with positive feedback. Conclusions: The digital technology proposed for occlusal splints in bruxism is reliable, and the rigid PMMA occlusal splints 3D printed are a viable alternative to conventional occlusal appliances in bruxism.